PENGEMBANGAN PENGENDALI PERANGKAT ELEKTRONIK DENGAN NODEMCU MELALUI BOT TELEGRAM - M. Purnomo Adji Saputro; Irwan Alnarus Kautsar; Arif Senja Fitrani; Suprianto Suprianto (Politeknik Bisnis Indonesia, 2024)
In the era of continuing globalization, technological progress is increasingly rapid and motivates people to compete in creating the latest breakthroughs. In this digitalization era, many innovations have emerged that can be maximized in everyday life, one of which is maximizing the Internet of Things with the Telegram application which can controlled via NodeMCU, which is an IoT-based open-source microcontroller that offers extraordinary flexibility and NodeMCU acts as a microcontroller that allows management of electronic devices, connected to Telegram bots operated by programmed software. In the research above, the author used the SDLC approach with the Waterfall method. This research discusses the development of controlling electronic devices with nodemcu via telegram bots as well as knowing the measurement of electrical power consumption when using them. The conclusion of this research shows that building a controller to control IoT-based electronic devices using an Android smartphone provides significant benefits. With this system, users can control devices remotely and at any time without having to approach a physical switch, very useful especially in multi-story buildings. Apart from that, this system also allows real-time measurement of electrical energy consumption, allowing users to monitor power consumption on electronic devices via Telegram bots